The Role of the Bone Marrow Study in Typhoid Fever with Pancytopenia - Getta, Hisham Arif (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background: Typhoid fever is an endemic infectious disease in Sulaimanyia city in Kurdistan region of Iraq. Last years we observe there are remarkable haematological changes associated with this disease. Pancytopenia was one of these changes. The aim of this study was to evaluate the role of bone marrow study in typhoid fever with pancytopenia. Methods: In this prospective study only culture positive enteric fever patients were taken. For all patients CBC and blood Film were done. Bone marrow study including aspirate and biopsy was done for all patients with peripheral blood pancytopenia. Result: Two thousands culture positive enteric fever patients were taken into this study. Presenting symptoms included mainly fever and rigor. The peripheral blood of these patients revealed different haematological changes, like normocytic anaemia, leucopenia, bicytopenia and pancytopenia. Pancytopenia was in 127 (6.3%) patients. Bone marrow was active in all patients. Histiocytes are increased in activity in 55 (43%) cases; only in 17 (13%) cases haemophagocytosis was seen. No granuloma seen in all cases. Majority of the patients regain the normal blood parameters values within two to eight weeks. Conclusion: Bone marrow study has no clear role for explanation the peripheral blood pancytopenia in typhoid fever. There is no indication for bone marrow study for culture positive typhoid fever with pancytopenia, unless the pancytopenia is persistent. Most probably the pancytopenia is caused by peripheral blood factor.